At navigere i et farefyldt hav - Lisdorf, Anders (Religionsvidenskabeligt Tidsskrift, 2004)
The Romans of republican times have traditionally been viewd as a rational and practical people for whom religion was of no real significance. In that view the elaborate Roman system for dealing with prodigies poses a problem, for why should something so apparently irrational and irreligious be invested with such a great amount of prestige and resources? Whereas earlier theories have tried to explain its existence either with reference to fear or to some stipulated function, this article argues that this cannot be the case, because there is no evidence for fear playing any central role and because a functional explanation cannot be sufficient. By an analysis of the workings of the system and the cultural models by which it was conceptualised, it is argued that for the Romans the purpose of the system was to secure success for the state, and thereby for each individual. This is achieved by a model connecting ritual and proper behaviour with portents and fortune/misfortune. In conclusion a comparison is made with the navigation procedures aboard a ship, and it is argued that the prodigy system and the navigation bridge serve the same overall function of navigating the seas of potential misfortune in order to keep the ship afloat, one figuratively and the other literally. Thus Roman culture can be seen as both practical and rational but also in essence religious.